The Social and Demographic Characteristics of Neurosurgical Patients with Drug-resistant Temporal Lobe Epilepsy - Galina Odintsova; Natalia Ivanova; Victoria Nezdorovina; Nina Dengina (Archives of Epilepsy)
Objective: In this study, our objective was to investigate the sociodemographic characteristics of patients with drug-resistant temporal lobe epilepsy (DR-TLE) undergoing neurosurgical management. Methods: The single-center, non-randomized, retrospective, parallel-group study was conducted in 2022-2023. The subject temporal DR-TLE. The object social and demographic indicators of neurosurgical patients. One hundred patients with DR-TLE after neurosurgical management were classified into two groups according to the type of surgical procedure. Results: Seventy-eight patients underwent resective surgery in group 1; twenty-two patients underwent destructive surgery in group 2. The mean age of the cohort was 32.3±8.18 years, with 53% of the patients being men and 47% women. The level of education in the cohort was characterised by a predominance of vocational qualifications (41%) compared to secondary education (24%) and tertiary education (34%). In group 1, the majority of patients had secondary vocational education; in group 2, patients with tertiary education predominated. There were twice as many unemployed people as employed people in the cohort, 64% and 31% respectively, indicating a difference between the groups. The percentage of patients with disabilities was 59%, indicating a predominance of patients with disabilities in group 1 and a predominance of patients without disabilities in group 2. The family situation was characterized by a low marital status (38%) and a mean age of 32.3±8.18 years, with no significant differences between the groups. Despite the reproductive age of the patients, the family situation and parental status were characterised by low rates of marriage and a low birth rate of 18%, with no differences between the groups. Conclusion: The group of neurosurgical patients was socially maladjusted: two-thirds were disabled and unemployed and only a quarter had a university degree. The trend toward late surgical management of drug-resistant temporal epilepsy continues. It is necessary to educate physicians and patients about the current possibilities of epilepsy surgery.